Racial gaps in child health insurance coverage in four south American countries: The role of wealth, human capital, and other household characteristics - Wehby, George (2011)
Objective. To evaluate the extent of racial gaps in child health insurance coverage in South America and study the contribution of wealth, human capital, and other household characteristics to accounting for racial disparities in insurance coverage. Data Sources/Study Setting. Primary data collected between 2005 and 2006 in 30 pediatric practices in Argentina, Brazil, Ecuador, and Chile. Design. Country-specific regression models are used to assess differences in insurance coverage by race. A decomposition model is used to quantify the extent to which wealth, human capital, and other household characteristics account for racial disparities in insurance coverage. Data Collection/Extraction Methods. In-person interviews were conducted with the mothers of 2,365 children. Principal Findings. The majority of children have no insurance coverage except in Chile. Large racial disparities in insurance coverage are observed. Household wealth is the single most important household-level factor accounting for racial disparities in coverage and is significantly and positively associated with coverage, followed by maternal education and employment/occupational status. Geographic differences account for the largest part of racial disparities in insurance coverage in Argentina and Ecuador. Conclusions. Increasing the coverage of children in less affluent families is important for reducing racial gaps in health insurance coverage in the study countries.